Studies on Germination of Spores of Bipolaris tetramera (Mckinney) Shoemaker - Sharma, Vishnupriya (Indian Forester, 2007)
In the present investigation the effect of different nutrient media and different pH levels on spore germination of Bipolaris tetramera (Mckinney) Shoemaker was studied. Single spore culture of B. tetramera obtained from diseased fruits of Coccinia indica Wight & Arn. Was employed for the present studies of spore germination and it was found that it took 5 hrs to produce the germ protuberance from both the polar cells of the test pathogen. Attempts done in this communication revealed that out of the five nutrient media tested viz. tap water, distilled water, 1% glucose solution, modified Asthana and Hawker's medium 'A' and host extract; it was the host extract which supported maximum germination of the test fungi but minimum germination occurred in tap water. Out of the twelve different pH levels tested (i.e. 2.0, 3.0, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 8.0, 9.0 and 10.0), it was found that no germination occurred at pH 2.0 while the maximum percent of germination was recorded at pH 5.5. As the spores are the main agents for propagating the disease thus the necessity of reporting the present findings is established.